Hubungan Asi Eksklusif dan BBLR dalam Pertumbuhan Bayi Usia 1-2 Tahun - Lestari, Endah Sri (Ridwan Institute, 2021)
To know relations breastfeeding exclusive and birth weight of low birth on the growth and development of toddlers age 1-2 years in the work area of community health center Leuwigajah 2019. this research is analytic by approach cross sectional. The population of the research is baby 1-2 age from April-May 2019 in the work area community health center Leuwigajah Cimahi about 45 baby. Using techniques sampling accidental sampling that is about 31 respondents using data analysis chi square test. respondents most exclusive obtain breastfeeding (68 %), experienced scene birth weight of low birth (87%), normal growth (84%), normal development (90%). Based on the data analysis bivariat the results that contact breastfeeding exclusively on the growth of (P=0,528)>(Î±= 0,05), breastfeeding exclusive relation to the development of (P=0,704)>(Î±=0,05), the relationship birth weight of low birth on the growth of (P=0,008)>(Î± = 0,05 ) and relations birth weight of low birth to the development of (P=0,037)>( Î±= 0,05) .We recommend that pregnant women always monitor their nutritional status in order to prevent the incidence of LBW and postpartum mothers are always supported to provide exclusive breastfeeding so as to support the optimal growth and development of toddlers in the golden periode.